Acute toxic complications of chemotherapy in children with acute lymphoblastic leukemia and acute myeloid leukemia: A systematic review - Jaxybayeva, Indira; Bazarbayeva, Aigul; Ospanova, Zhanna; Karimova, Kymbat; Khashimova, Zukhra; Manarbekova, Zhanna; Genzhegulova, Madina; Daurenova, Korkem (Acta Biomedica Atenei Parmensis, 2026)
Background: Intensive chemotherapy for childhood acute lymphoblastic leukemia (ALL) and acute myeloid leukemia (AML) is associated with substantial toxicity that affects treatment tolerability and outcomes. Aim: To summarize the evidence on acute chemotherapy-related toxic complications in children with ALL and AML. Methods: This systematic review was conducted in accordance with PRISMA guidelines; the protocol was registered in PROSPERO (CRD420251248980). A literature search was performed in PubMed, Web of Science, Scopus, and Google Scholar for studies published between 2000 and 2025. Studies involving patients with newly diagnosed ALL or AML receiving polychemotherapy and reporting acute toxic effects were included. Owing to substantial heterogeneity across studies, no meta-analysis was performed. After screening 614 records, 70 studies were included in the review. Results: The most frequently reported complications were infectious, hematologic, gastrointestinal, hepatic, neurologic, renal, cardiac, thrombotic, and metabolic toxicities. The highest rates of severe toxicity were observed during induction and early consolidation. Infectious complications remained the leading cause of severe morbidity and treatment-related mortality, particularly in AML. In ALL, marked interstudy variability was noted in the reported rates of mucositis, neurotoxicity, hepatotoxicity, and toxicities associated with methotrexate, vincristine, and asparaginase, whereas in AML, severe infectious, respiratory, and cardiotoxic events predominated in the setting of highly intensive treatment regimens. The risk of complications depended on leukemia subtype, treatment phase, protocol composition, patient age, cumulative drug exposure, and supportive care practices. Conclusion: Systematizing these data is important for the early identification of high-risk patients, optimization of monitoring strategies, and improvement of supportive care.